P366 Exclusive enteral nutrition drives protective microbiome modulation in paediatric Crohn's Disease. (21st January 2022) - Häcker, D; Siebert, K; Metwaly, A; Hölz, H; De Zen, F; Köhler, N; Pauling, J K; Matchado, M; List, M; Schwerd, T; Haller, D
Abstract: Background: Exclusive enteral nutrition (EEN) is a first-line induction therapy for paediatric Crohn's disease (CD). Although the protective mechanisms remain unclear, previous studies showed substantial changes in microbiome composition in response to EEN. We aim to assess the protective function of EEN and its impact on gut microbiome signatures in paediatric CD. Methods: We prospectively followed, 15 newly diagnosed paediatric CD patients aged, 3–18 years between, 01/2019 –, 08/2021. Patients were treated according to international guidelines including EEN therapy for, 6–8 weeks, followed by a gradual re-introduction of solid food and concomitant start of maintenance treatment. Disease activity and inflammatory biomarkers were monitored during, 12-months follow-up. 16S rRNA gene sequencing and targeted/untargeted metabolomics was performed from stool samples collected weekly during EEN and monthly thereafter (n = 261). Dietary modulation and clinical activity of patient-derived stool microbiota were studied by ex-vivo faecal fermentation and after faecal microbiota transplantation (FMT) into germ free (GF) IL10 -/- mice. Results: All patients achieved remission with EEN therapy but, 6/15 had resuming CD activity within, 6 months. Longitudinal microbial and metabolite profiling of stool samples showed highly individualized responses to EEN without coherent signatures. Integrated multi-omics data analysis showed an enrichment of long-chain fatty acids in patients under EEN, which correlated with a reduced abundance of Lachnospiraceae, compared to patients under regular diet. Faecal microbiota from CD patients with active disease (baseline or relapse) or inactive disease (EEN-induced remission) were exposed to EEN-like or dietary control formulations in continuous ex-vivo cultures. EEN-like formulation induced protective changes in the patient-derived baseline microbiota confirmed by the absence of disease activity after FMT in GF IL10 -/- mice. Mice colonized with baseline microbiota after ex-vivo EEN exposure showed a decreased abundance of Bacteroides, Akkermansia, Blautia and an increase of Lachnoclostridium and Parabacteroides in comparison to those colonized directly with patient's baseline microbiota. In contrast, EEN-like diet failed to mitigate the aggressive behaviour of relapse microbiota when transferred into GF IL10 -/- mice which was in line with an inability to cause significant compositional changes. Conclusion: Our data show that clinical efficacy of EEN in paediatric CD is accompanied by temporal and individual gut microbial and metabolite changes. The combined findings of continuous culture and gnotobiotic mouse models point towards a direct protective role of EEN-modulated patient microbiomes in regulating intestinal inflammation.